Contributos para inevitável revisão da legislação militar em Portugal - Silva, Pedro Alexandre dos Santos (2021)
The Military Discipline Regulation (RDM) applies the armed forces in order to guarantee their situation and the way of providing services, the same in the situations in which the functio provision of services, there are cases where the situation is not ef ns of the organizational structure are exposed. "Even if the military are already in reserve for the effectiveness of the fective, the terms are legally admitted." There have been cases in which there is no responsibility to make use of the uniform, when there is no legal consent, admitted, as evidenced in no. 3 and 4 of article 5 of the RDM.) The military hierarchy, as contemplated in article 1 of the Regulation of May 2, 1913, "Is the moral bond that connects it with one another." It is born of dedication, of duty and constancy, and of punctual observation of military laws and regulations. " According to the same Regulation, it is achieved "by the conviction of the mission to be fulfilled and maintained by the prestige arising from the principles of justice employed, respect for the rights of all, the exact fulfillment of duties, knowledge, correction of proceeding and of mutual esteem ". These are still the fundamental principles in which they determine military discipline, an essential condition for the fulfillment of the historical and national mission entrusted to the Armed Forces and without which it would not be and will not be possible to survive in any quadrant. However, as a projection of these principles, the regulatory norms governing the Armed Forces do not crystallize; before they evolve according to social evolution itself. According to Article 1 of the same law, "The organization and activity of the Armed Forces are based on the fundamental military values of mission, hierarchy, cohesion, discipline, security and obedience to the competent organs of sovereignty in accordance with the Constitution and the law. "In paragraph 2, it states that" Military discipline shall ensure respect for fundamental military values while respecting the ethical principles of virtue and honor inherent in the military condition. " good functioning within the Armed Forces, military discipline is the "essential way" for its efficiency and effectiveness, so that as soon as it fulfills its purpose regularly, namely the "Defense of the Motherland".